2022
DOI: 10.1609/aaai.v36i9.21231
|View full text |Cite
|
Sign up to set email alerts
|

Qubit Routing Using Graph Neural Network Aided Monte Carlo Tree Search

Abstract: Near-term quantum hardware can support two-qubit operations only on the qubits that can interact with each other. Therefore, to execute an arbitrary quantum circuit on the hardware, compilers have to first perform the task of qubit routing, i.e., to transform the quantum circuit either by inserting additional SWAP gates or by reversing existing CNOT gates to satisfy the connectivity constraints of the target topology. The depth of the transformed quantum circuits is minimized by utilizing the Monte Carlo tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In 2020, Pozzi et al [29] extended the method proposed by Herbert et al [28] , using double deep Q-learning and prioritized experience replay to optimize the quantum circuit mapping. Zhou et al [30] in 2020 and Sinha et al [31] in 2022 also combined the Monte Carlo tree algorithm for qubit routing in the quantum circuit mapping process. Although these methods provided a more suitable way to add SWAP gates for quantum circuit 2DNN architecture mapping, they ignored the impact of the initial placement of logical qubits in the mapping process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2020, Pozzi et al [29] extended the method proposed by Herbert et al [28] , using double deep Q-learning and prioritized experience replay to optimize the quantum circuit mapping. Zhou et al [30] in 2020 and Sinha et al [31] in 2022 also combined the Monte Carlo tree algorithm for qubit routing in the quantum circuit mapping process. Although these methods provided a more suitable way to add SWAP gates for quantum circuit 2DNN architecture mapping, they ignored the impact of the initial placement of logical qubits in the mapping process.…”
Section: Introductionmentioning
confidence: 99%
“…And recently Peham et al [34] compared the performance of various advanced quantum circuit mapping algorithms on benchmarks of known optimal mapping, and concluded that even the most advanced algorithms are not capable of optimal solutions therefore exists to improve upon them. Inspired by the Monte Carlo tree search algorithm [31] and the graph isomorphism search algorithm, [35] this paper proposes a 2DNN architecture mapping method of quantum circuits based on deep reinforcement learning. In our proposed DRL scheme, a new state representation and learning paradigm is adopted, which helps to improve the SWAP gate addition of the output quantum circuit and has faster algorithm running speed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this challenge, previous studies have proposed approximate solutions that use methods like A* search [19][20][21], Monte Carlo tree search [22,23], simulated annealing [24][25][26], reinforcement learning [27,28], and heuristics [7,14,[29][30][31][32][33][34][35][36][37][38][39][40]. Some of these approximate solutions have been implemented in qiskit [41] and tket [42], and have good scalability with respect to the problem size (i.e., the number of qubits and gates).…”
Section: Introductionmentioning
confidence: 99%
“…• 1 additional shuttle operation for each Z rotation gate Depth overhead.FIG. 7: Shuttle-based SWAP for two-qubit gate routing: With this technique, two diagonally neighbouring qubits exchange their position by consecutively performing two horizontal and two vertical shuttles.equal to the minimum number of time steps of a circuit when executing gates in parallel[9,10,[45][46][47]. We calculate depth overhead as the percentage relation of additional depth produced by the mapper to the circuit depth after decomposition.…”
mentioning
confidence: 99%